Answer:
{10,8}
Step-by-step explanation:
-3x + 4y = -62
4x + 5y = 0
let's eliminate the x
-3x + 4y = -62 | x -4 |
4x + 5y = 0 | x 3 |
12x - 16y = 248
12x + 15y = 0
-------------------- -
-31y = 248
y = 248/(-31) = 8
since you must do this proble with elimination, we cant use subtitution. so we repeat the way once more to find x (eliminate y)
-3x + 4y = -62 | x 5 |
4x + 5y = 0 | x 4 |
-15x + 20y = -310
16x + 20y = 0
-------------------- -
-31x = -310
x = -310/-31 = 10
Answer:
x = 2, y = 1
Step-by-step explanation:
x + 4y = 6 and y = 3 - x have to be rearranged: x + 4y = 6 and x + y = 3
You subtract the equations to eliminate one of the variables (x) so that the other can be found
Answer:
52.4
Step-by-step explanation:
Arc length = 2πr(θ/360)
r = 10
θ = 300°
Arc length = 2π(10)(300/360) = 20π(0.8333) = 16.666π ≈ 52.36
Answer:
40%
Step-by-step explanation:
Percentage Passed = 36 ÷ 90 × 100 = 40%